Extraction of natural bioactive compounds using clean label technologies and their application as muscle food preservatives - Rathod, Nikheel Bhojraj; Nirmal, Nilesh Prakash; Abdullah, Sajeeb; Surasani, Vijay Kumar Reddy; Ranveer, Rahul Chudaman; Kumar, Siddhnath; Chunhavacharatorn, Phatchada; Benjakul, Soottawat; Al-Asmari, Fahad (Frontiers in Sustainable Food Systems, 2023)
Muscle foods are the main source of high protein and mineral content. However, these foods are highly perishable due to their high moisture content as well as nutritional composition. Generally, microbial changes and oxidative damage occurs during animal slaughter and storage. To avoid this quality deterioration, various chemical additives are widely practiced by the industry. Nevertheless, consumer awareness and government strict regulation on synthetic additives demand clean label foods. The potential of natural bioactive compounds exhibiting strong antioxidant and antimicrobial properties for food preservation is a promising area of research. Recently, the interest in the non-thermal extraction process of bioactive compounds is growing due to their various advantages in extraction yield, stability, and bioactivity of the compound. Besides this, a natural bioactive compound can be applied in combination with other hurdle technologies to enhance the shelf-life of muscle foods. Therefore, this review article emphasizes the current knowledge on the novel non-thermal extraction of bioactive compounds from natural sources and their application as a muscle food preservative. Application of antioxidant and antimicrobial compounds from natural sources alone and in combination with other hurdle technologies has been successfully used for preservation of muscle foods. Additionally, different application methods and their impact on muscle food preservation are suggested.